The Relationship of Social Networking to the Academic Performance of Third Year Pamantasan ng Lungsod ng Maynila-College of Nursing Students: An Assessment - Dytuco, Dennis C.; Manio, Mariam Wilbeth T.; Nepomuceno, Rose Ann T.; Raon, Roselle Lara G.; Reotutar, Joyce Junevive G.; Sengco, Joshua L.; Tesil, Mark Jheric D. and Tiglao, Rizza Mae B. 4 0 16; 5 (2011)
u
Undergraduate (Thesis) Pamantasan ng Lungsod ng Maynila.;College of Nursing, Bachelor of Science in Nursing.
Keywords: 2 -- 0; 6; 20; 20; 2